C4d detection in renal allograft biopsies: immunohistochemistry vs. immunofluorescence - Santos,Ana (2012)
Introduction. Peritubular capillary complement 4d staining is one of the criteria for the diagnosis of antibody-mediated rejection, and research into this is essential to kidney allograft evaluation. The immunofluorescence technique applied to frozen sections is the present gold-standard method for complement 4d staining and is used routinely in our laboratory. The immunohistochemistry technique applied to paraffin-embedded tissue may be used when no frozen tissue is available. Material and Methods.The aim of this study is to evaluate the sensitivity and specificity of immunohistochemistry compared with immunofluorescence. We describe the advantages and disadvantages of the immunohistochemistry vs. the immunofluorescence technique. For this purpose complement 4d staining was performed retrospectively by the two methods in indication biopsies (n=143) and graded using the Banff 07 classification. Results.There was total classification agreement between methods in 87.4% (125/143) of cases. However, immunohistochemistry staining caused more difficulties in interpretation, due to nonspecific staining in tubular cells and surrounding interstitium. All cases negative by immunofluorescence were also negative by immunohistochemistry. The biopsies were classified as positive in 44.7% (64/143) of cases performed byimmunofluorescence vs. 36.4% (52/143) performed by immunohistochemistry. Fewer biopsies were classified as positive diffuse in the immunohistochemistry group (25.1% vs. 31.4%) and more as positive focal (13.2% vs. 11.1%). More cases were classified as negative by immunohistochemistry (63.6% vs. 55.2%). Study by ROC curve showed immunohistochemistry has a specificity of 100% and a sensitivity of 81.2% in relation to immunofluorescence (AUC: 0.906; 95% confidence interval: 0.846-0.949; p=0.0001). Conclusions.The immunohistochemistry method presents an excellent specificity but lower sensitivity to C4d detection in allograft dysfunction. The evaluation is more difficult, requiring a more experienced observer than the immunofluorescence method. Based on these results, we conclude that the immunohistochemistry technique can safely be used when immunofluorescence is not available